If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2t + 5 = 8 Reorder the terms: 5 + 2t = 8 Solving 5 + 2t = 8 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2t = 8 + -5 Combine like terms: 5 + -5 = 0 0 + 2t = 8 + -5 2t = 8 + -5 Combine like terms: 8 + -5 = 3 2t = 3 Divide each side by '2'. t = 1.5 Simplifying t = 1.5
| x+3+x+3=10 | | .33x=1017 | | 16x+3y=3 | | .25x=866 | | -6=5(x+3)-6x | | -6=(x+3)+6x | | .33x=.25x | | -6=(x+3)+4x | | c^2-7c-12=0 | | c^2-35-60=0 | | 11x=64+36 | | 2x-3+2x-3=1 | | 5c^2-35c=60 | | 9x=56+2x | | x^4-4*x^3=0 | | x=2x+8 | | x^2-8xy+16y^2-25=0 | | 12p=12p+4 | | u^2+49=2u^2-6u+64 | | p-4=p+p | | (7x)(3x^9u^6)(2u^4)= | | 2x+3=36x | | x^3-x^2=0 | | s^2-7x-8=0 | | 4y+3y=(2)+4y | | 9a^4-a^2b^2=0 | | 8s^2-2x-3=0 | | x^2-5x-6=3 | | 4s^2+s=3 | | 4y+3+y=(y+2)+4 | | 4s^2+9x-9=0 | | s^2-6x-7=0 |